Efeito dos óleos essenciais de Syzygium aromaticum e Cinnamomum zeylanicume e seus compostos majoritários na produçao de biofilme em cepas de Staphylococcus aureus, isolados de leite de vacas com mastite subclínica - Budri, Paulo Eduardo [UNESP] (2014)
Bovine Mastitis is an inflammation of the mammary gland of cows causing economic losses in dairy cattle and Staphylococcus aureus is one of the microorganisms most commonly isolated in this kind of disease. The production of biofilms by S. aureus is an important virulence factor and spreed of this microorganism, involving the adhesion of bacteria on solid surfaces. In this work we tested the essential oils of Syzygium aromaticum (OESA) and Cinnamomum zeylanicum (OECZ) and their major compounds, eugenol and cinnamaldehyde, as the activity on biofilm formation in strains of S. aureus on different surfaces. The results showed a significant inhibition (p <0.05) for the biofilm production on the by OESA on polystyrene and stainless steel surface (69.4% and 63.6 %, respectively). However, its major compound, eugenol, did not show the same effectiveness, reducing in only 52.8 % and 19.6 % in polystyrene stainless steel (p > 0.05). On the other hand, OECZ and its major compound, cinnamaldehyde, reduced significantly the capacity of biofilm production, both in polystyrene (74.7% and 69.6%, respectively) and on the of stainless steel surfaces (45.3% and 44.9%, respectively). Due to the significant reduction of biofilm production by OESA, OECZ and cinnamaldehyde, at low concentration, these substances may be considered as active ingredient, in the production of sanitizers in the food industry